Sorption Characteristics of Pea Seeds - Garg, M K; Chandra, Pitam (Journal of Agricultural Engineering, 2003)
An experiment was conducted to study the equilibrium moisture characteristics of pea seeds under adsorption and desorption. Four three-parameter equations were selected for the analysis of equilibrium moisture content (EMC) - equilibrium relative humidity (ERH) data of pea seeds. The selected equations were compared using statistical parameters. The values of EMC for both adsorption and desorption decreased with increase in temperature. Sorption isotherms were found to be sigmoid in shape. The modified-Oswin equation was found best suited to EMC-ERH data of pea seeds.